Both external and internal factors induce heterogeneity in senescing leaves of deciduous trees - Mattila, Heta (CSIRO Publishing, 2025)
Autumn senescence is characterised by spatial and temporal heterogeneity. We show that senescing birch (Betula spp.) leaves had lower PSII activity (probed by the F V /F M chlorophyll a fluorescence parameter) in late autumn than in early autumn. We confirmed that PSII repair slows down with decreasing temperature, while rates of photodamage and recovery, measured under laboratory conditions at 20°C, were similar in these leaves. We propose that low temperatures during late autumn hinder repair and lead to accumulation of non-functional PSII units in senescing leaves. Fluorescence imaging of birch revealed that chlorophyll preferentially disappeared from inter-veinal leaf areas. These areas showed no recovery capacity and low non-photochemical quenching while green veinal areas of senescing leaves resembled green leaves. However, green and yellow leaf areas showed similar values of photochemical quenching. Analyses of thylakoids isolated from maple (Acer platanoides ) leaves showed that red, senescing leaves contained high amounts of carotenoids and α-tocopherol, and our calculations suggest that α-tocopherol was synthesised during autumn. Thylakoids isolated from red maple leaves produced little singlet oxygen, probably due to the high antioxidant content. However, the rate of PSII photodamage did not decrease. The data show that the heterogeneity of senescing leaves must be taken into account to fully understand autumn senescence.